Identification and variation analysis of the composition and content of essential oil and fragrance compounds in Phoebe zhennan wood at different tree ages - Yang, Hanbo; Zhang, Shuaiying; Gu, Yunjie; Peng, Jian; Huang, Xin; Guo, Hongying; Chen, Lianghua; Jiang, Yongze; Liu, Minhao; Luo, Xiandan; Xie, Jiaxin; Wan, Xueqin (Frontiers in Plant Science, 2024)
Wood essential oil and wood products with special fragrances are high value-added forest products. Despite the availability of essential oil and volatile organic compounds (VOCs) from Phoebe zhennan wood, their variation and dependence on tree age have not been examined. After essential oil extraction and wood processing, the yields and compositions of essential oils and VOCs in wood from P. zhennan trees of different ages (10a, 30a, and 80a) were determined. The yield of essential oil from 30a wood was significantly greater than that from 10a and 80a wood. Liquid chromatography–mass spectrometry (LC‒MS) and gas chromatography‒mass spectrometry (GC‒MS) revealed 672 and 41 volatile compounds, respectively, in the essential oil and wood, the majority of which exhibited large fluctuations in relative content and composition depending on tree age. Sesquiterpenoids, fatty acids and conjugates may greatly contribute to the main components of essential oil from wood. Almost all major sesquiterpenoid compounds, such as caryophyllene α-oxide, eudesmo, and cubebene, were identified in the essential oils from the 30a and 80a wood, and their relative contents were much greater than those in the 10a wood. The main components of the wood fragrance were sesquiterpenoids. The types and relative contents of sesquiterpenoids from wood increased with tree age. These results suggest that choosing wood from trees of a suitable age will significantly improve the efficiency of wood utilization.